Emotions, work and care on the border between the public and the domestic sphere (Quinto Sol, 2024)
This dossier addresses the relationship between emotions, work and care from a historicized perspective that focuses on motherhood. The articles that comprise it study the emotional geographies in border spaces between the public and domestic domains, and problematize how work is intertwined with the experiences of motherhood, regulated by prescriptions and emotional styles crossed by asymmetries of gender, migratory origin, class, and also institutional and professional asymmetries. Some of the axes that run through the dossier are emotional work, the relevance of affectivity in migratory experiences, both transnational and internal, and the disputes around models of maternity, as well as the capacity to adjust or resist to social norms and expectations. The conceptual scaffolding of the history of emotions allows us to discuss the concept of maternal love as universal and immutable, to recognize the variety and complexity of family experiences, and to explore the tensions between normative script and emotional practice.
Keywords: Emotions Work Care Matherhood